2018
DOI: 10.1111/tbed.12868
|View full text |Cite
|
Sign up to set email alerts
|

Papillomaviruses in ruminants: An update

Abstract: Papillomaviruses (PVs) are complex viruses which infect the skin or mucosae of a broad range of amniotes worldwide. They cause benign or malignant lesions depending on environmental factors, virus oncogenicity and the location of infection. Bovine papillomaviruses (BPVs) are the second most studied PVs beyond human PVs. In the past few years, genetic characterization of animal PVs has increased due to the availability of new techniques, which simplified the sequencing of entire genomes. Therefore, this review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 91 publications
(237 reference statements)
1
53
0
6
Order By: Relevance
“…A total of 57% of the samples analysed showed similarity with viral type BPV2, which is associated with tumours in the urinary tract (Borzacchiello et al, 2007;Balcos et al, 2008;Resendes et al, 2011). This viral type has the greatest geographic distribution and has been reported in countries such as Germany, Brazil, New Zealand, Japan, India, Italy, Turkey and Korea and isolated from cutaneous papillomas, pulmonary fibromatosis, bladder, semen, blood, milk and urine (Daudt et al, 2018). These samples related to BPV2 Figure 2.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A total of 57% of the samples analysed showed similarity with viral type BPV2, which is associated with tumours in the urinary tract (Borzacchiello et al, 2007;Balcos et al, 2008;Resendes et al, 2011). This viral type has the greatest geographic distribution and has been reported in countries such as Germany, Brazil, New Zealand, Japan, India, Italy, Turkey and Korea and isolated from cutaneous papillomas, pulmonary fibromatosis, bladder, semen, blood, milk and urine (Daudt et al, 2018). These samples related to BPV2 Figure 2.…”
Section: Resultsmentioning
confidence: 94%
“…BPV1 and BPV2 have also been identified from equine sarcoids in horses as a result of transmission between species (Ataseven et al, 2016;Daudt et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Xipapillomavirus genus has two species: Xipapillomavirus 1 (BPV-3, BPV-4, BPV-6, BVP-9, BPV-10, BPV-11, and BPV-15) and Xipapillomavirus 2 (BPV-12). The other two genus are Epsilonpapillomavirus 1 (BPV-5 and BPV-8) and Dyoxypapillomavirus 1 (BPV-7) [ 1 , 10 , 11 , 12 , 13 ]. Lastly, two recently described types (BPV-17) and BPV-20) are still unclassified as species.…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of these genomes are of animal origin, including those of viruses from cervid species. Most of these viruses are species-specific [5,6], but cross-infections have also been reported [5,[7][8][9]. It was reported that some animal species are often infected by PVs belonging to different taxonomic groups [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PVs are responsible for skin and mucosa infections of humans and various animals, in which they can appear asymptomatic or cause different neoplastic changes, ranging from self-limited warts to cancers [5,10,12,13]. In cervids, most of the detected PVs belong to the Deltapapillomavirus genus and cause neoplastic changes described as fibromas, papillomas, fibropapillomas or warts [15].…”
Section: Introductionmentioning
confidence: 99%